The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/2016ja022348
|View full text |Cite
|
Sign up to set email alerts
|

Wide field‐of‐view soft X‐ray imaging for solar wind‐magnetosphere interactions

Abstract: Soft X‐ray imagers can be used to study the mesoscale and macroscale density structures that occur whenever and wherever the solar wind encounters neutral atoms at comets, the Moon, and both magnetized and unmagnetized planets. Charge exchange between high charge state solar wind ions and exospheric neutrals results in the isotropic emission of soft X‐ray photons with energies from 0.1 to 2.0 keV. At Earth, this process occurs primarily within the magnetosheath and cusps. Through providing a global view, wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 63 publications
2
33
0
1
Order By: Relevance
“…They also showed that peak emissions along lines-of-sight that pass through the subsolar magnetosheath exceed background levels for all but the lowest solar wind plasma fluxes. Walsh et al (2016b) described the process by which realistic global images of soft Xray images from the magnetosheath and cusps can be simulated for wide field-of-view imagers at specified locations. First the magnetospheric contribution is calculated using plasma values from a global magnetohydrodynamic simulation and neutral densities from an exospheric model.…”
Section: Past Modeling Effortsmentioning
confidence: 99%
“…They also showed that peak emissions along lines-of-sight that pass through the subsolar magnetosheath exceed background levels for all but the lowest solar wind plasma fluxes. Walsh et al (2016b) described the process by which realistic global images of soft Xray images from the magnetosheath and cusps can be simulated for wide field-of-view imagers at specified locations. First the magnetospheric contribution is calculated using plasma values from a global magnetohydrodynamic simulation and neutral densities from an exospheric model.…”
Section: Past Modeling Effortsmentioning
confidence: 99%
“…Recently, a novel approach was proposed to remotely detect the large‐scale magnetopause: soft X‐ray imaging (Branduardi‐Raymont et al, , ; Collier et al, ; Sibeck et al, ; Walsh et al, ). The basic mechanism for soft X‐ray emissions in the magnetosheath and cusp regions is the solar wind charge exchange (SWCX) process.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this discrepancy, MHD models do a poor job of simulating both the size of the emitting region and the emission strength. Walsh et al (2016b) found that the density of the cusp in MHD simulations is usually less than half that of the cusp density as measured by the Polar mission. The observed cusp has an opening angle of ∼ 4 • , which roughly half as wide (in latitude) as the cusp produced by MHD simulations.…”
Section: The Cuspsmentioning
confidence: 90%
“…Were it possible to model SWCX emission for an arbitrary time and look direction, the history of SWCX research would not be over. Remote sensing of the solar wind and direct imaging of the magnetosheath are exciting possibilities for space physicists Walsh et al 2016b). As we will see in the following sections, modeling is still far from successful.…”
Section: Curbing the Chaosmentioning
confidence: 99%